Lung, Pleural, and Mediastinal Biopsies: From Preprocedural Assessment to Technique and Management of Complications - Larocque, Natasha; Brook, Olga R. (Seminars in Interventional Radiology, 2022)
Biopsies of the lung, pleura, and mediastinum play a crucial role in the workup of thoracic lesions. Percutaneous image-guided biopsy of thoracic lesions is a relatively safe and noninvasive way to obtain a pathologic diagnosis which is required to direct patient management. This article reviews how to safely perform image-guided biopsies of the lung, pleura, and mediastinum, from the preprocedural assessment to reviewing intraprocedural techniques, and how to avoid and manage complications.
Keywords: interventional radiology; percutaneous; lung biopsy; pleural biopsy; mediastinal biopsy